A barking dog never talks: animals in Machado de Assis’ novels - Pádua, Vitória Saramago (Revista de Letras, 2008)
One of the most interesting aspects of the novel Philosopher or dog? is, certainly, the relationship established between its protagonist Rubião and his dog Quincas Borba. There is a mixture of dialogue and monologue, in which Rubião seems to listen clearly to the dog’s words. However, such words serve only to confirm thoughts and feelings of the protagonist himself. Even considering its significant differences, something similar occurs with other characters in Machado de Assis’ novels: Aires attributes reflexions to dogs and asses, Brás Cubas interacts with butterflies, Bentinho with worms. Taking into account the fables’ tradition, from Aesope to La Fontaine, in which animals act as an inverted mirror of human mind, it is appropriate to ask if Machado might be rethinking or even subverting this genre in his works. Therefore, this article examines some new dimensions given to the lafontainian fable, from the perspective of the subjectivity’s configurations and the narrator’s specificity in Machado’s works. Animals will be analyzed, thus, as spaces where human subjectivity may be unfolded.